Spatial ecology of host-parasitoid interactions: A threatened butterfly and its specialised parasitoid - Klapwijk, M; Lewis, O (Kluwer Academic Publishers, 2014)
Habitat conservation for threatened temperate insect species is often guided by one of two paradigms: a metapopulation approach focusing on patch area, isolation and number; or a habitat approach focusing on maintaining high quality habitat for the focal species. Recent research has identified the additive and interacting importance of both approaches for maintaining populations of threatened butterflies. For specialised host-parasitoid interactions, understanding the consequences of habitat characteristics for the interacting species is important, because (1) specialised parasitoids are particularly vulnerable to the consequences of fragmentation, and (2) altered interaction frequencies resulting from changes to habitat management or the spatial configuration of habitat are likely to have consequences for host dynamics. The spatial ecology of Cotesia bignellii, a specialist parasitoid of the threatened butterfly Euphydryas aurinia, was investigated at two spatial scales: within habitat patches (at the scale of individual aggregations of larvae, or 'webs') and among habitat patches (the scale of local populations). Parasitism rates were investigated in relation to larval web size, vegetation sward height and host density. Within patches, the probability of a larval webs being parasitized increased significantly with increasing number of larvae in the web, and parasitism rates increased significantly with increasing web isolation. The proportion of webs parasitized was significantly and negatively correlated with cluster density. Among habitat patches the proportion of parasitized webs decreased as cluster density increased. Clusters with a high proportion of larval webs parasitized tended to have lower parasitism rates per larval web. These results support the call for relatively large and continuous habitat patches to maintain stable parasitoid and host populations. Conservation efforts directed towards maintenance of high host plant density could allow E. aurinia to reduce parasitism risk, while providing C. bignellii with sufficient larval webs to allow population persistence. © 2014 Springer International Publishing Switzerland.